CHF6297: a novel potent and selective p38 MAPK inhibitor with robust anti-inflammatory activity and suitable for inhaled pulmonary administration as dry powder - Martucci, Cataldo; Allen, Andrew Dennis; Moretto, Nadia; Bagnacani, Valentina; Fioni, Alessandro; Patacchini, Riccardo; Civelli, Maurizio; Villetti, Gino; Facchinetti, Fabrizio (Frontiers in Pharmacology, 2024)
Inhibition of p38 mitogen-activated protein kinase (MAPKs) is a potential therapeutic approach for the treatment of acute and chronic pulmonary inflammatory conditions. Here, we report the in vitro and in vivo characterization of the anti-inflammatory effects of CHF6297, a novel potent and selective p38α inhibitor designed for inhalation delivery as a dry powder formulation. CHF6297 has been proven to inhibit p38α enzymatic activity with sub-nanomolar potency (IC50 = 0.14 ± 0.06 nM), with >1,000-fold selectivity against p38γ and p38δ. In human peripheral blood mononuclear cells (PBMCs) stimulated with lipopolysaccharides (LPS), as well as in human bronchial epithelial cells (BEAS2B) stimulated with TNF-α or cigarette smoke extract (CSE), CHF6297 inhibited interleukin (IL)-8 release with low nanomolar potency. CHF6297 administered to rats by using a nose-only inhalation device as a micronized dry powder formulation blended with lactose dose-dependently inhibited the LPS-induced neutrophil influx in the bronchoalveolar lavage fluid (BALF). CHF6297 administered intratracheally to rats dose-dependently counteracted the IL-1β (0.3 mg/kg)-induced neutrophil influx (ED50 = 0.22 mg/kg) and increase in IL-6 levels (ED50 = 0.82 mg/kg) in the BALF. In mice exposed to tobacco smoke (TS), CHF6297, administered intranasally (i.n.) for 4 days at 0.03 or 0.3 mg/kg, dose-dependently inhibited the corticosteroid-resistant TS-induced neutrophil influx in the BALF. In a murine house dust mite (HDM) model of asthma exacerbated by influenza virus A (IAV) (H3N3), CHF6297 (0.1 mg/kg, i.n.) significantly decreased airway neutrophilia compared to vehicle-treated IAV/HDM-challenged mice. When CHF6297, at a dose ineffective per se (0.03 mg/kg), was added to budesonide, it augmented the anti-inflammatory effects of the steroid. Overall, CHF6297 effectively counteracted lung inflammation in experimental models where corticosteroids exhibit limited anti-inflammatory activity, suggesting a potential for the treatment of acute exacerbations associated with chronic obstructive pulmonary disease (COPD) and asthma, acute lung injury (ALI), and viral-induced hyperinflammation.